Curation, Compliance, Consolidation: Understanding the Limits of Innovation Policy’s Turn to Creativity - O. Osbild, Nadine; Pfotenhauer, Sebastian (NOvation — Critical Studies of Innovation, 2025)
In recent years, innovation policy has increasingly turned to creativity as a resource for economic revitalization, social cohesion and sustainability transitions. In urban redevelopment, creative districts blend innovation logics of a “creative class” and “transformative innovation” with experimental urban governance to address grand challenges and enable broader societal transformation. Building on critiques of the idea that innovation and creativity function as “magic bullets” in the contemporary economy (Pratt & Jeffcutt, 2009) , we explore the limits of this transformative promise in this article. Our analysis is grounded in ethnographic fieldwork across four creative district projects in Munich, Germany, where normative visions of creativity and innovation are rendered legitimate and governable. Through the conceptual lens of regional innovation cultures (Pfotenhauer et al., 2023) , we examine how the creativity-innovation-nexus is locally stabilized and tamed through distinct cultivation mechanisms, summarized as curation, compliance, and consolidation, that reinscribe existing socio-political settlements and market-driven valuation logics of the common good. Paradoxically, Munich’s creative districts foster a form of conservative creative innovation that constrains the transformative potential of creative innovation by reproducing hegemonic power structures and marginalizing alternative visions of conviviality (Robra et al., 2023). We argue that creative districts—and similar initiatives—risk undermining their potential as open, experimental spaces for radical transformation when they prioritize innovation’s productive role over creativity’s more politically contested and disruptive capacities.